Circular Orbits Around Static Spherically Symmetric Configuration with Linear Massive Scalar Field in General Relativity - Жданов, Валерій Іванович; Твардовський, Денис (Київський національний університет імені Тараса Шевченка, 2025)
Background. Theories with scalar fields are widely discussed in various generalizations of the Standard cosmological model dealing with the inflation of the Universe, dynamical dark energy, Hubble tension etc. Introduction of a scalar field in static spherically symmetric (SSS) asymptotically flat gravitational system causes the appearance of specific features in the distribution of stable circular orbits, which may lead to observational effects in the accretion disk structure. We study this distribution in the case of a massive scalar field in the framework of General Relativity. Methods. We consider the Einstein equations with minimally coupled massive scalar field resulting in the ordinary differential system that is solved numerically (SSS case). This solution is applied to study the distribution of stable circular orbits of test bodies using properties of an effective potential for the test-body motion. Results. There are two main regions around the asymptotically flat SSS configuration with scalar field: a weak-field region, where we have an approximate analytical description of the problem and usual distribution of circular orbits as in case of the Schwarzschild metric, and a scalarization region with a significant deviation of the metric from the Schwarzschild case. In the scalarization region, a numerical solution for the linear scalar field with the corresponding metric coefficients is derived. Analytical relations to study the test body circular orbits are obtained. We show that, for a wide range of masses of the linear scalar field and astrophysically relevant configuration masses, there either exists a region of weakly stable circular orbits near the center, or there are no circular orbits in the scalarization region at all. Conclusions. The distribution of stable circular orbits is significantly different from the case of a Schwarzschild black hole. In case of sufficiently large masses of the scalar field and configuration masses, the circular orbits in the scalarization region will be virtually absent. This suggest a similar conclusion about the structure of accretion disks.

Вступ. Теорії зі скалярними полями широко обговорюють в узагальненнях Стандартної космологічної моделі, що стосуються інфляції Всесвіту, динамічної темної енергії, Hubble Tension тощо. Введення скалярного поля в статичну сферично-симетричну (SSS) асимптотично плоску гравітаційну систему зазвичай призводить до особливостей розподілу стабільних колових орбіт, які можуть бути пов’язані зі спостережними ефектами. Ми вивчаємо цей розподіл у випадку масивного скалярного поля в межах загальної теорії відносності. Методи. Ми розглядаємо рівняння Ейнштейна з мінімально зв’язаним масивним скалярним полем, що призводить до звичайної диференціальної системи, яка розв’язується чисельно (випадок SSS). Цей розв’язок застосовують для вивчення розподілу стабільних колових орбіт пробних тіл на основі властивостей ефективного потенціалу. Результати. Навколо асимптотично плоскої конфігурації SSS є дві основні області: область слабкого поля, де ми маємо наближений аналітичний опис розв’язку та звичайний розподіл колових орбіт, як у випадку метрики Шварцшильда, та область скаляризації зі значним відхиленням метрики від метрики Шварцшильда. В області скаляризації отримано числові розв’язки для скалярного поля з відповідними метричними коефіцієнтами. Отримано аналітичні співвідношення для дослідження колових орбіт пробного тіла. Ми показуємо, що для широкого діапазону мас скалярного поля й астрофізично релевантних конфігураційних мас або існує область слабкостабільних кругових орбіт поблизу центра, або кругові орбіти в області скаляризації взагалі відсутні. Висновки. Розподіл стабільних колових орбіт суттєво відрізняється від випадку чорної діри Шварцшильда. Для достатньо великих мас скалярного поля та конфігураційних мас колові орбіти в області скаляризації будуть практично відсутні. Це дозволяє зробити аналогічний висновок щодо структури акреційних дисків.
Колові орбіти навколо статичної сферично-симетричної конфігурації з лінійним масивним скалярним полем у загальній теорії відносності
Keywords: релятивістські об’єкти; голі сингулярності; модифікована гравітація; elativistic objects; naked singularities; modified gravity